2001
DOI: 10.1128/mcb.21.1.26-38.2001
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Receptor Substrate 3 (IRS-3) and IRS-4 Impair IRS-1- and IRS-2-Mediated Signaling

Abstract: To investigate the roles of insulin receptor substrate 3 (IRS-3) and IRS-4 in the insulin-like growth factor 1 (IGF-1) signaling cascade, we introduced these proteins into 3T3 embryonic fibroblast cell lines prepared from wild-type (WT) and IRS-1 knockout (KO) mice by using a retroviral system. Following transduction of IRS-3 or IRS-4, the cells showed a significant decrease in IRS-2 mRNA and protein levels without any change in the IRS-1 protein level. In these cell lines, IGF-1 caused the rapid tyrosine phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
1
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(66 citation statements)
references
References 54 publications
2
62
1
1
Order By: Relevance
“…Ad5E1A and IRS proteins NJ Shimwell et al transformed lines that express IRS-4. Such a reciprocal relationship between IRS-1 and IRS-4 has been reported previously (Tsuruzoe et al, 2001). Experiments to determine the half-life of IRS-4 in the presence or absence of E1A showed that E1A expression did not have an effect (data not shown).…”
Section: Regulation Of Irs-4 Expressionsupporting
confidence: 84%
“…Ad5E1A and IRS proteins NJ Shimwell et al transformed lines that express IRS-4. Such a reciprocal relationship between IRS-1 and IRS-4 has been reported previously (Tsuruzoe et al, 2001). Experiments to determine the half-life of IRS-4 in the presence or absence of E1A showed that E1A expression did not have an effect (data not shown).…”
Section: Regulation Of Irs-4 Expressionsupporting
confidence: 84%
“…A similar increase in PTEN promoter activity was also observed in NIH3T3 cells (data not shown). The IGF axis is able to induce the transcription factor egr-1 in embryonic and cardiac fibroblasts (31,32), and we have recently shown that egr-1 directly activates PTEN during irradiation-induced signaling to a similar magnitude as observed above (12). Therefore, we investigated the requirement of egr-1 for IGF-II regulation of PTEN transcription.…”
Section: Igf-ii Effect Is Epithelial Cell Autonomous-bothmentioning
confidence: 94%
“…It induces IGF-II promoter expression in HepG2 cells in response to hypoxia (36). Also, stimulation of IGF signaling induces egr-1 expression, an effect that may be dependent on IRS-1 (31,32). Thus, egr-1 is both upstream and downstream of IGF-II signaling.…”
Section: Igf-ii Effect Is Epithelial Cell Autonomous-bothmentioning
confidence: 99%
“…Taken together, these animal studies document that the IRS family proteins have quite distinct biological roles and functional redundancy does not appear to be a major issue in this protein family. A recent study even suggests that the IRS-3 and IRS-4 proteins can impair rather than complement the signalling of their relatives IRS-1 and -2 (Tsuruzoe et al, 2001).…”
Section: Irs Proteinsmentioning
confidence: 99%